Survei Kemampuan Renang Gaya Bebas 50 Meter Pada Mahasiswa Program Studi Pendidikan Olahraga STIKIP Kie Raha - Mahatma Raison Pribadi; Fijai Madilis (Jurnal Ilmiah Wahana Pendidikan, 2022)
The aims of this research are: 1). To determine the 30 meter freestyle swimming ability of STKIP Kie Raha sports education students. Methods This research is a quantitative descriptive study that uses survey methods and data collection techniques using tests and measurements, so as to provide an overview of what will be examined in the form of numbers and measured with certainty. Based on observations in the 50-meter freestyle swimming sport for STKIP Kie Raha sports education students, the results of freestyle swimming ability varied between very poor and very good. The results of the tabulation of scores obtained from 20 male students, as contained in the table above shows that the criteria for students who have a value of 18.07 < X (very poor), as many as 4 people (20%) then at a value of 16.04 < X 18, 07 (less) obtained as many as 2 people (10%), then in the category (enough) with a value of 14.01 < X 16.04 obtained 12 students (60%), a value of 12.25 < X 14.01 with category (good), as many as 2 people (10%), and at X 12.25 with category (very good), no one was able to achieve that score.